Students’ perception of teaching methods in pharmacology in a Malaysian medical school / Renu Agarwal and Nafeeza Mohd Ismail - Agarwal, Renu; Mohd Ismail, Nafeeza (Faculty of Medicine, 2016)
Introduction: The study attempts to evaluate the students’ perception of pharmacology as a subject, its usefulness in future practice, teaching methods currently used, and their patterns of learning and preparing for exams. Methods: A structured, self-administered questionnaire was distributed to second year medical students. Results: Of the 125 students who participated, 22.73 % considered pharmacology more important than any other subject. The students found small group sessions most interesting followed by directed self-learning, computer aided learning and lectures. Of those who responded, 79 and 66 % suggested to increase the small group and directed-self-learning sessions respectively. Up to 40 % of the students felt that pharmacology teaching must be through case-based discussions and 20 % requested for more practical sessions. Conclusions: It appears that majority of students entering the medical schools has little prior knowledge of pharmacology. While going through the preclinical years they understood the importance of pharmacology and its application in future practice, however, they tend to develop interest in one or other topics. Students prefer to have a greater number of small group sessions as they feel that these sessions are most useful for learning. Majority of the students tend to use both the textbooks and lecture notes and study regularly for better performance in examinations. The students also preferred to have more case-based learning sessions incorporated into the small group sessions.